(untitled) (Majalah Kedokteran Bandung, 2014)
Kasus multi drug resistant tuberculosis (MDR TB) terus meningkat. Penatalaksanaan klinis MDR TB lebih rumit dibandingkan dengan TB sensitif karena menggunakan obat anti-TB lini I dan lini II, sehingga menyebabkan permasalahan toleransi dan efek samping. Desain penelitian ini kohort yang bertujuan untuk mengetahui jenis, frekuensi, dan faktor risiko efek samping obat. Pelaksanaan penelitian dilakukan antara Januari 2011–Juni 2013. Suspek MDR TB diambil sputum, dilakukan pengecatan Ziehl Nielsen, dilanjutkan pemeriksaan Xpert MTB/RIF pada regio gen rpoB untuk menentukan resistensi rifampisin. Selanjutnya uji resistensi obat anti-TB dengan menggunakan media padat (Lowenstein Jensen) dan media cair Mycobacteria growth indicator tube test (MGIT). Penelitian dilakukan di RS Dr. Moewardi. Jumlah pasien yang terkonfirmasi MDR TB adalah 114 orang: 56 laki-laki dan 58 perempuan. Efek samping terbanyak gangguan gastrointestinal: mual 79,8%, muntah 78,9%. Sebagian besar efek samping derajat ringan 76,3%. Terdapat hubungan antara riwayat pengobatan TB dan gangguan renal (p=0,026), antara jenis kelamin dan gangguan renal (p=0,033) serta gangguan pendengaran (p=0,039). Tidak terdapat hubungan antara jenis kelamin dan gangguan psikiatri (p=0,062), antara riwayat pengobatan TB dan gangguan pendengaran (p=0,115) serta hipokalemia (p=0,968). Simpulan, efek samping terbanyak adalah gangguan gastrointestinal. Kata kunci: Efek samping, gangguan gastrointestinal, MDR TB, pendengaran, renal Multidrug Resistant Tuberculosis (MDR-TB): Epidemiologic Review and Adverse Events Risk Factors of Anti Tuberculosis Drugs Abstract The number of Multi drug resistant tuberculosis (MDR-TB) cases is predicted to be increasing. The management of MDR-TB is more complex than susceptible TB due to the resistance to the first and second lines of anti tuberculosis drugs. Leading to anti tuberculosis drugs tolerance and adverse event issues. This study was a cohort study conducted between January 2011 and June 2013 to describe the type, frequency, and risk factors of adverse events caused by drugs. Sputum samples of patients who were suspected to have MDR TB were collected and examined as sputum smears using Ziehl Nielsen staining and Gene Xpert MTB/RIF segment amplification of rpoB gene region methods to assess resistance towards rifampicin. Samples with positive results were cultured in solid medium (Lowenstein Jensen) and liquid medium (Mycobacteria growth indicator tube test,MGIT). This study was conducted in Moewardi General Hospital. The number of confirmed MDR-TB patients was114 subject consisting of 56 males and 58 females. The most common adverse events were gastrointestinal disturbances including nausea 79.8% and vomiting 78.9%. Minor adverse events also found in 76.3% patients. There was a significant relationship between previous anti tuberculosis medication and renal impairment (p=0.026); between sex and renal impairment (p=0.033); and between sex and hearing impairment (p= 0.039). There was no significant relationship between sex and mental illnesses (p=0.062) as well as between previous anti tuberculosis medication and hearing impairment (p=0.115) and between previous anti tuberculosis medication and hypopotassemia (p=0.968),. In conclusion, the major adverse events in MDR-TB cases are gastrointestinal disturbances Key words: Adverse events, gastrointestinal disturbance, hearing impairment, MDR-TB, renal impairment DOI: 10.15395/mkb.v46n4.336